Спектральныe характеристики твердых и мягких согласных русского и литовского языков - Балшайтите, Д. (Kalbotyra, 1991)
The article deals with acoustic parametres of velar-palatal idiosyncrasy of Lithuanian and Russian consonants. Velar and palatal consonants are characterized as having special acoustic features which reveal themselves regulary in the spectre of the consonant. At the same time spectral features of Lithuanian consonants are dependent on the quality of the consonant as well as on the following vowel and because of this reason they cannot serve is indicators of velar and palatal qualities.